Penyuluhan dan Edukasi Kosmetik yang Aman Bersama HIASKOS di SMKN 8 Makassar - Ainun Jariah; Yuri Pratiwi Utami; Imrawati Imrawati; Rahmah Mustarin; Indah Meilani AS; Nurzadrina Wahyuddin; Yuniar Dwi Yanti (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Cosmetics are substances or preparations used on the external parts of the human body (epidermis, hair, nails, lips, and external genital organs) primarily for cleansing, perfuming, altering appearance, or improving body odor, or for protecting or maintaining the body's health. Providing counselling and education on safe cosmetics to teenagers is not just about giving beauty tips; it's a crucial step in protecting their long-term health. Adolescents are in a phase of physical and hormonal transition that makes them very concerned about their appearance, but they often lack sufficient consumer literacy to distinguish between safe and harmful products. This counselling aims to educate students to be wiser in choosing safe cosmetics. The method used is direct socialization to students at SMKN 8 Makassar, providing counselling to assess the improvement in understanding after education, direct socialization, and socialization using leaflets. The results obtained show an increase in participants' knowledge of how to choose and use appropriate and safe daily cosmetics. The conclusion of this service activity is that the counselling on safe cosmetics is highly relevant and well-received by adolescents, and it is able to improve their understanding of safe cosmetics, so similar activities can be expanded to other locations.